2017
DOI: 10.1002/adem.201700095
|View full text |Cite
|
Sign up to set email alerts
|

Phase Stability of a Mechanically Alloyed CoCrCuFeNi High Entropy Alloy

Abstract: A CoCrCuFeNi high entropy alloy (HEA) is prepared from the high purity elemental Co,Cr, Cu,Fe, and Ni powders by mechanical alloying (MA) at different milling speed (200 or 350 rpm). Mechanically alloyed powder samples are subsequently annealed at different temperatures (300, 500, 700, and 800 C). Microstructures, chemical composition, and phase stability of the powders are studied using X-ray Diffraction (XRD), Scanning Electron Microscopy (SEM), and energy dispersive X-ray spectrometry (EDS). The results sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(25 citation statements)
references
References 38 publications
1
21
0
Order By: Relevance
“…Meanwhile, we compare the calculated lattice constants with available experimental and theoretical data for CrFeCoNi and CrFeCoNiCu HEAs, as listed in Table 1. It can be found that the corresponding theoretical predications are 3.578Å and 3.590Å, respectively, which are very close to the previous experimental data for CrFeCoNi and CrFeCoNiCu HEAs, [40][41][42][43][44] and the theoretical data for CrFeCoNi HEA, 42,45 the comparison results verify the validity of the theoretical analysis method.…”
Section: Resultssupporting
confidence: 83%
“…Meanwhile, we compare the calculated lattice constants with available experimental and theoretical data for CrFeCoNi and CrFeCoNiCu HEAs, as listed in Table 1. It can be found that the corresponding theoretical predications are 3.578Å and 3.590Å, respectively, which are very close to the previous experimental data for CrFeCoNi and CrFeCoNiCu HEAs, [40][41][42][43][44] and the theoretical data for CrFeCoNi HEA, 42,45 the comparison results verify the validity of the theoretical analysis method.…”
Section: Resultssupporting
confidence: 83%
“…Moreover, a small content of Ni was also found in some particles. The contamination of Fe and Cr from the vial and balls is a very common problem in MA . Powder B (Figure B) is homogenous and slightly contaminated by Fe and Cr.…”
Section: Summary Of Results Of Alcrfemnmo Alloymentioning
confidence: 99%
“…TaNbHfZrTi 4 , NbTaVWZr 5 etc.) or face-centered cubic (FCC) (e.g., CoCrCuFeNi 6 , CoCrFeMnNi 7 etc.) solid solutions.…”
Section: Introductionmentioning
confidence: 99%